Research on Milling Characteristics of Titanium Alloy TC4 with Variable Helical End Milling Cutter - Xiangming Hu; Hanying Qiao; Mingyu Yang; Yaoman Zhang (Machines, 2022)
The application of variable helical end mills to the milling of titanium alloys can suppress the regeneration effect during the machining process and ensure the stability of milling. However, due to their special geometry, their milling characteristics are also different. In this paper, the process of milling titanium alloy with a variable helix end mill is taken as the research object, and the milling force, milling stability and machining effect during the machining process are deeply studied. Firstly, the feed per tooth and cutting thickness model of the variable helical end mill were established, the milling force prediction model of the variable helical end mill was deduced, and the instantaneous milling force and its variation law were obtained by solution. Secondly, the finite element analysis model of the variable helix end mill for machining titanium alloy was established, and the influence of the variable helix angle structure on the milling force was obtained. Then, the dynamic equation of milling with a variable helix end mill was established, the stability lobe diagram of variable helix milling is was and drawn, and the influence of variable helix angle on milling stability was analyzed. Lastly, a variable helix end mill milling experiment was designed to verify the accuracy of the theoretical model and finite element simulation; the influence of the variable helix angle structure on the surface roughness was analyzed, and the influence of machining parameters on the milling force when using a variable helix end mill was investigated.